A Novel Anti-Cancer Therapy: CRISPR/Cas9 Gene Editing - Chen, Xin-Zhu; Guo, Rong; Zhao, Cong; Xu, Jing; Song, Hang; Yu, Hua; Pilarsky, Christian; Nainu, Firzan; Li, Jing-Quan; Zhou, Xin-Ke; Zhang, Jian-Ye (Frontiers in Pharmacology, 2022)
Cancer becomes one of the main causes of human deaths in the world due to the high incidence and mortality rate and produces serious economic burdens. With more and more attention is paid on cancer, its therapies are getting more of a concern. Previous research has shown that the occurrence, progression, and treatment prognosis of malignant tumors are closely related to genetic and gene mutation. CRISPR/Cas9 has emerged as a powerful method for making changes to the genome, which has extensively been applied in various cell lines. Establishing the cell and animal models by CRISPR/Cas9 laid the foundation for the clinical trials which possibly treated the tumor. CRISPR-Cas9-mediated genome editing technology brings a great promise for inhibiting migration, invasion, and even treatment of tumor. However, the potential off-target effect limits its clinical application, and the effective ethical review is necessary. The article reviews the molecular mechanisms of CRISPR/Cas9 and discusses the research and the limitation related to cancer clinical trials.